OPTIMIZING MOMI BOBA BEVERAGE BUSINESS PERFORMANCE THROUGH ENTERPRENEURIAL LEADERSHIP - Rosyida, Zulma Aini; Mashudi; Asiyah , Binti Nur (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Momi Boba Ice, which was founded in 2022, is a beverage business that was founded with the aim of building a beverage business. In this research, the observation method was used to collect information about the business. Observation results show that Momi Boba Ice is more focused on selling drinks. The superior drink variants are chocolate and cappuccino. Apart from that, Momi Boba Ice requires an average of 50 kg of sugar every month and still has 1 branch in Sumbergempol since it was founded by Rosidatul Khusna in 2022. Through entrepreneurial leadership it can help the Momi Boba Ice business optimize its performance and growth with strategies appropriate entrepreneurial leadership strategy. For example, using effective marketing strategies to increase sales of beverage products and reduce production costs through supply chain optimization. The application of entrepreneurial leadership can also help this business overcome challenges that may occur in the future, such as fluctuations in raw material prices and increasingly fierce competition in the beverage market